2022
DOI: 10.1101/2022.02.22.481532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of claustrum on cortex varies by area, layer, and cell type

Abstract: The claustrum is a small subcortical structure with widespread connections with disparate regions of the cortex. These far-reaching projections have led to many hypotheses concerning its function. However, we know little about how claustrum input affects neural activity in cortex, particularly beyond frontal areas. Here, using optogenetics and multi-regional Neuropixels recordings from over 15,000 neurons in awake mice, we demonstrate that the effect of claustrum input differs depending on brain area, layer, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Our final set of experiments sought to investigate the regional and laminar differences of CLA innervation of the cortex as well as the types of sensory-related information CLA axons convey to their cortical targets. Recent in vivo electrophysiological evidence points toward differences in excitatory and inhibitory tone elicited by excitation of CLA cell bodies that varies by cortical area and layer (9, 51). Other studies in single cortical regions find more uniform responses to CLA inputs, generally inhibitory (73, 74), although electrophysiological studies in cats have found more variable or bidirectional responses in visual cortices (75, 76).…”
Section: Discussionmentioning
confidence: 99%
“…Our final set of experiments sought to investigate the regional and laminar differences of CLA innervation of the cortex as well as the types of sensory-related information CLA axons convey to their cortical targets. Recent in vivo electrophysiological evidence points toward differences in excitatory and inhibitory tone elicited by excitation of CLA cell bodies that varies by cortical area and layer (9, 51). Other studies in single cortical regions find more uniform responses to CLA inputs, generally inhibitory (73, 74), although electrophysiological studies in cats have found more variable or bidirectional responses in visual cortices (75, 76).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, perturbing the CLA-medial prefrontal pathway suggest that this pathway is involved in regulating impulsivity (Lui et al, 2019), attentional set-shifting (Fodoulian et al, 2020), and salience detection (Atlan et al, 2018; Terem et al, 2020), while optogenetic interrogating of the CLA-ACA pathway suggests that this pathway modulates engagement with the external world (Atlan et al, 2021). Optically activating CLA principal neurons of transgenic lines in the awake head-fixed mice on freely moving-wheel shows that neuronal responses differ in different layers and cell types of various cortical areas (prefrontal cortex, ACA, MOs and RSP) (McBride et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our definition of the mouse CLA meets anatomical criteria and is consistent with a developmental study, which uses gene expression patterns to mark only one group of neurons underneath of the AI (Watson and Puelles, 2017), and with a combination of tract-tracing and immunohistochemical studies (Barbier et al,2019;Qadir et al, 2018;Suárez et al, 2018), similar to what has been used for rat CLA (Mathur et al, 2009(Mathur et al, , 2014. The accurate delineation of the boundary of the mouse CLA studies lays a solid foundation for a better understanding of its cell types, circuits, and functions as in the companion paper (McBride et al, 2022).…”
Section: Delineation Of the Boundary Of The Mouse Clamentioning
confidence: 99%
See 2 more Smart Citations